Complete Convergence for Moving Average Process of Martingale Differences - Wenzhi Yang; Shuhe Hu; Xuejun Wang (Discrete Dynamics in Nature and Society)
Under some simple conditions, by using some techniques such as truncated method for random variables (see e.g., Gut (2005)) and properties of martingale differences, we studied the moving process based on martingale differences and obtained complete convergence and complete moment convergence for this moving process. Our results extend some related ones.